Current trends in digital camera-based bioassays for point-of-care tests - Pohanka, Miroslav (Clinica chimica acta, 2024)
Point-of-care and bedside tests are analytical devices suitable for a growing role in the current healthcare system and provide the opportunity to achieve an exact diagnosis by an untrained person and in various conditions and sites where it is necessary. Using a digital camera integrated into a well-accessible device like a smartphone brings a new way in which a colorimetric point-of-care diagnostic test can provide unbiased data. This review summarizes basic facts about the colorimetric point-of-care tests, principles of how to use a portable device with a camera in the assay, applications of digital cameras for the current tests, and new devices described in the recent papers. An overview of the recent literature and a discussion of recent developments and future trends are provided.
Keywords: lidé; kolorimetrie; point of care testing; chytrý telefon; Humans; Point-of-Care Testing; Colorimetry; Smartphone